Conference at Saint Tikhon’s Orthodox University “Digitalization of Society and the Future of Christianity” - Igor Ryazantcev; Vasiliy Pisarevskiy (Journal of Economic Sociology, 2019)
The conference “Digitalization of Society and the Future of Christianity” was held at St. Tikhon's Orthodox Humanitarian University. Digital technologies are now rapidly becoming a part of society, exerting an active influence on social processes. Different researchers describe this transformation of social reality in different ways, such as “The Fourth Industrial Revolution” (Klaus Schwab) or “technological singularity” (Ray Kurzweil). However, we must focus not just on the “sum of technologies” but, above all, on how these changes morph our perception of society and how they affect the economy and politics. The development of digitalization has its advantages — for example, an increase in productivity — and risks, such as the reduction of jobs for both workers and highly qualified employees. At the same time, there exists another important question: how can we assess digitalization from a spiritual and moral point of view? How does it affect the individual and suppress his or her freedom? In a recent interview, Patriarch Kirill of Moscow and all Russia noted the danger of gadgets that“provide not just access to personal information but its use.” The danger of using personal data, noted by Patriarch Kirill, is only one aspect of digitalization. Attempts to use biometrics, the development of robotics, 3D printing, augmented reality and several other technologies raise further questions. The conference also touched upon the development of legislative initiatives in relation to the process of digitalization. We discussed the development of draft laws relating to a number of modern digital technologies as well as the creation of a favorable legal environment for our country to gain a competitive advantage in the international digital market. The international conference “Digitalization of Society and the Future of Christianity” will be held annually at St. Tikhon's Orthodox Humanitarian University.